Minimum indoor temperature threshold recommendations for English homes in winter – A systematic review. (July 2016) - Jevons, R.; Carmichael, C.; Crossley, A.; Bone, A.
Abstract: Objectives: To identify and assess the available evidence on the impacts of cold indoor temperature thresholds on human health and make evidence-based recommendations for English homes. Study design: Systematic literature review. Methods: A systematic search of peer-reviewed published literature from the UK and countries with similar climates, and grading of the evidence using the National Institute of Health (NIH) framework was followed by a discussion with experts and formulation of recommendations. Results: Twenty papers were included. Studies were included if they were conducted outside England but were from countries considered to have similar climates. Studies included two small randomised controlled trials, two cohort studies and one case control study; other studies were cross-sectional, largely laboratory-based studies. Health effects in the general population start to occur at around 18 °C. Effects in older people are more profound than in younger adults. Older people are less able to perceive low temperatures. Discussion: Although evidence was limited, a strong argument for setting thresholds remains. The effects observed on the general population and the effects on those more vulnerable makes a case for a recommended minimum temperature for all. Health messages should be clear and simple, allowing informed choices to be made. A threshold of 18 °C was considered the evidence based and practical minimum temperature at which a home should be kept during winter in England. Conclusion: There is limited evidence available on minimum temperature thresholds for homes. However a recommendation of at least 18 °C for the whole population with nuancing of messages for those more vulnerable to the effects of cold can be made from the results of the retrieved studies. Recommendation: Heating homes to at least 18 °C (65 °F) in winter poses minimal risk to the health of a sedentary person, wearing suitable clothing.